1998
DOI: 10.1007/s004050050018
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a local recurrence of a carcinoid tumor of the middle ear by extended subtotal petrosectomy

Abstract: A recurrence of a primary carcinoid tumor of the middle ear 15 years after radical tympanomastoidectomy is reported. An extended subtotal petrosectomy using a craniocervical approach with temporary infracondylar mandibulotomy was performed, since imaging studies demonstrated an extensive tumor with a close relationship to the tegmen tympani, facial nerve, and ascending and horizontal portions of the carotid canal. The tumor was metabolically inactive. Histopathological examination showed a solid, trabecular tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…Ramsey et al reported a case with facial paresis associated with invasion of the facial nerve and an intraneural spread [10]. Knerer et al reported another patient who required facial nerve sacrifice because of tumor involvement [11]. The carcinoid tumor belongs to the group of APUDomas (Amine Precursor Uptake and Decarboxylation) or endocrine cell tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Ramsey et al reported a case with facial paresis associated with invasion of the facial nerve and an intraneural spread [10]. Knerer et al reported another patient who required facial nerve sacrifice because of tumor involvement [11]. The carcinoid tumor belongs to the group of APUDomas (Amine Precursor Uptake and Decarboxylation) or endocrine cell tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Local recurrence following attempts at curative excision is uncommon, but has been observed [13]. An unusual carcinoid tumor of the middle ear was described which occurred 1 year after the removal of a primary carcinoid of the ileum [14].…”
Section: Carcinoid Tumorsmentioning
confidence: 98%
“…However, patients with extensive osteolytic spread of a middle-ear carcinoid as in the current subject have been reported [3, 4, 8, 9]. The MRI findings of the carcinoid tumors may not be useful for differentiation from other inflammatory diseases and other tumors; however, dynamic enhanced MRI in the present case showed carcinoid tumors to be enhanced earlier after the administration of Gd than granulation and other types of normal tissue.…”
Section: Discussionmentioning
confidence: 51%
“…One patient was initially treated with a petromastoidectomy for a tumor in the hypotympanicum extending into the external auditory canal without bone destruction [8], and another patient initially underwent a partial petrosectomy for the removal of middle-ear tumors extending into the hypotympanicum with partial erosion of the stapes superstructure [9]. Knerer et al described surgical treatment by extended subtotal petrosectomy for an extensive recurrent tumor with a close relationship to the tegmen tympani, facial nerve, and the ascending and horizontal portions of the carotid canal [3]. Menezes et al performed a craniotomy, petrosectomy, neck dissection, and parotidectomy for a recurrent carcinoid tumor, but the carcinoid tumor recurred within 3 months after the surgery [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation